Pendampingan Penerapan Protokol Kesehatan Di Masa Era New Normal Pada Kumpulan Pengajian Kelompok Wanita Tani Di Desa Saronggi - Cory Nelia Damayanti; Dian Ika Puspitasari; Emdat Suprayitno (Poltekkes Kemenkes Surakarta, 2021)
Background: In 2020, Indonesia experienced a pandemic period, during which the corona virus spread. Close contact is a factor in the transmission of the covid 19 virus. Applying health protocols is considered important to reduce the incidence of the increase in the covid 19 virus. Methods: The basic purpose of this service is to provide training and assistance in implementing health protocols for community groups, especially the recitation group for farmer women's groups in the village of Saronggi. The main purpose of this service is to suppress the spread of the corona virus in the community. Results: The results showed that the counseling and mentoring process at the Women's Farmer's Association in Saronggi village went smoothly and as expected. This can be seen from the enthusiasm of all members when listening to counseling and changes in the behavior or habits of members in implementing health protocols when carrying out activities Conclusions Suggestions that we can hope for are to remain disciplined with health protocols so that they can really suppress the spread of the virus and break the chain of the Corona Virus.